PREVALÊNCIA E FATORES DE RISCO ASSOCIADOS AO ALEITAMENTO MATERNO EXCLUSIVO ATÉ OS SEIS MESES DE IDADE - de Morais Junior, Carlos Pires (2014)
It is known that maternal breastfeeding is a physiological process in which the mother gives to her child the nutrients in the correct proportions at this early stage of life and it is common sense that has great importance for the development of the baby, and there is also an improvement the immunity of the child. Based on these facts this research aims to assess the prevalence and risk factors associated with exclusive breastfeeding until six (06) months of age. This is a descriptive study of mothers of children up to one year. The variables involved are exclusively breastfed for six months had AIDS, education level of the mother, need to work early, pre-natal, firstborn, problems related to breast milk and breastfeeding. The statistical analysis will be by frequency of occurrence of each variable.